Norway House: Economic Opportunity and the Rise of Community, 1825-1844. - McKillip, James D. (Université d'Ottawa / University of Ottawa, 2012)
This dissertation argues that the Hudson’s Bay Company depot that was built at Norway House beginning in 1825 created economic opportunities that were sufficiently strong to draw Aboriginal people to the site in such numbers that, within a decade of its establishment, the post was the locus of a thriving community. This was in spite of the lack of any significant trade in furs, in spite of the absence of an existing Aboriginal community on which to expand and in spite of the very small number of Hudson’s Bay Company personnel assigned to the post on a permanent basis. Although economic factors were not the only reason for the development of Norway House as a community, these factors were almost certainly primus inter pares of the various influences in that development. This study also offers a new framework for the conception and construction of community based on documenting day-to-day activities that were themselves behavioural reflections of intentionality and choice. Interpretation of these behaviours is possible by combining a variety of approaches and methodologies, some qualitative and some quantitative. By closely counting and analyzing data in archival records that were collected by fur trade agents in the course of their normal duties, it is possible to measure the importance of various activities such as construction, fishing and hunting. With a clear understanding of what people were actually doing, it is possible to interpret their intentions in the absence of explicit documentary evidence.
Keywords: fur trade; Rupert's Land; micro-history; western Canada; colonialism; British Empire; Canadian Aboriginal; Metis; Hudson's Bay Company; economic history